The Static Structure and Dynamics of Cadmium Sulfide Nanoparticles within Poly(styrene‐block‐isoprene) Diblock Copolymer Melts. Issue 4 (20th December 2015) - Jang, Woo‐Sik; Koo, Peter; Bryson, Kyle; Narayanan, Suresh; Sandy, Alec R.; Russell, Thomas P.; Mochrie, Simon G.
Abstract : The static structure and dynamic behavior of cadmium sulfide nanoparticles suspended in block copolymer matrix are investigated using transmission electron microscopy, small‐angle X‐ray scattering, and X‐ray photon correlation spectroscopy. The transmission electron microscopy study shows that cadmium sulfide nanoparticles are preferentially segregated within the polyisoprene domain of a poly(styrene‐ block ‐isoprene) diblock copolymer. For the dynamics study, X‐ray photon correlation spectroscopy captures the relaxation process of cadmium sulfide nanoparticles. The measured characteristic relaxation time reveals that the observed dynamics are hyperdiffusive. The characteristic velocity and corresponding activation energy, which are hallmarks of a hyperdiffusive system, are determined from the relationship between the characteristic relaxation time and the wavevector. Abstract : The equilibrium structures and dynamics of cadmium sulfide nanoparticles suspended in block copolymer matrix are investigated via transmission electron microscopy, small‐angle X‐ray scattering, and X‐ray photon correlation spectroscopy. The transmission electron microscopy shows the preferential segregation of nanoparticles. X‐ray studies reveal a particular hyperdiffuisve dynamics.